1986
DOI: 10.1080/07315724.1986.10720146
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding and insulin-dependent diabetes mellitus in children.

Abstract: We have evaluated the hypothesis of a protective effect of human milk on the development of insulin dependent diabetes mellitus (IDDM). We studied the feeding histories of 95 diabetic children and compared them with controls consisting of their non-diabetic siblings and a pair matched group of nondiabetic peers of the same age, sex, geographical location, and social background. The incidence of breast feeding in diabetic children was 18%. This was similar to the control group. The duration of breast feedings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 4 publications
0
33
1
2
Order By: Relevance
“…Although this observation was not confirmed by three subsequent studies [87][88][89], two additional studies published in 1988, one from Australia [90] and the other from the United States (Colorado) [91], support the original report [86]. An association between extent and duration of breast-feeding and lower incidence of IDDM was subsequently reported in other studies from Sweden [92], Finland [93], Hungary [94], and the United States [95].…”
Section: Breast-feeding and Incidence Of Iddmmentioning
confidence: 59%
“…Although this observation was not confirmed by three subsequent studies [87][88][89], two additional studies published in 1988, one from Australia [90] and the other from the United States (Colorado) [91], support the original report [86]. An association between extent and duration of breast-feeding and lower incidence of IDDM was subsequently reported in other studies from Sweden [92], Finland [93], Hungary [94], and the United States [95].…”
Section: Breast-feeding and Incidence Of Iddmmentioning
confidence: 59%
“…Several groups, working in both human and animal models, set about trying to confirm this finding with inconsistent results. Fort et al could find no relationship between breast-feeding history and T1D [120] while others found that children with diabetes had been breast-fed over less time, on average, than non-diabetic children [121][122][123]. Similarly, a two-fold increase in diabetes incidence has been observed when the duration of breast-feeding was less than 3-4 months [reviewed in 124,125,107], or when the infant was exposed to CM formula before 2-3 months of age [126,127].…”
Section: Cow's Milk (Cm) Proteinsmentioning
confidence: 99%
“…They proposed that breast-feeding provides maternal antibodies to prevent diabetogenic infections [25]. Three studies from Italy, New York, and the United Kingdom failed to support the hypothesis [26][27][28].…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…The associations found in those studies suggesting a link to duration of breast-feeding are marginal with odds ratios in the 1.4 to 1.8 range [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Nutritional Factorsmentioning
confidence: 99%